Exotic Design in Industrial Products: A Comparative Study of Iraqi and Indonesian Consumer Taste - Alhilo, Mahmad Hasan Hayawi (Universitas Komputer Indonesia, 2025)
As a result of the political, social, economic, scientific changes that have happened in the twentieth century, a new thinking, new arts have became appeared and the companies competition, encouraged designers to create innovative product forms including exotic product designs. One of them is the ceramic cup, a functional and universal product used across cultures, with design variations. Cups were chosen as the object of research because it is relevant to measure differences in design preferences across two contrasting cultures. This research compares the preference of Indonesians and Iraqis to find out the design criteria that are of concern to each. The urgency of this comparison lies in the significant cultural differences between Asia and the Middle East, as well as the huge market potential in both countries with the rapid growth of the creative industry. The method used is comparative. The research population was Indonesian and Iraqi interior design students, with purposive sampling technique. Data collection through questionnaires, respondents were asked to rank the most favorite designs, then the results were analyzed using Statistical Package for the Social Sciences (SPSS) and using the evaluation criteria (key Jury criteria) for product design from the Cairo Design Award (CDA 2023) to analyze product characteristics. The results show that both Indonesia and Iraq prioritize creativity, innovation, novelty, and originality, which can be considered universal factors interest of products. The difference lies in visual communication is more important for Indonesian, while innovation is the main attraction for Iraqi consumers, this is reflecting the cultural background. Keywords: Exotic Product Design, Consumer Preference, Cultural Comparison, Design Criteria